Single Nucleotide Polymorphism Charting of P. patens Reveals Accumulation of Somatic Mutations During in vitro Culture on the Scale of Natural Variation by Selfing - Haas, Fabian B.; Fernandez-Pozo, Noe; Meyberg, Rabea; Perroud, Pierre-François; Göttig, Marco; Stingl, Nora; Saint-Marcoux, Denis; Langdale, Jane A.; Rensing, Stefan A. (Frontiers in Plant Science, 2020)
Introduction Physcomitrium patens (Hedw.) Mitten (previously known as Physcomitrella patens) was collected by H.L.K. Whitehouse in Gransden Wood (Huntingdonshire, UK) in 1962 and distributed across the globe starting in 1974. Hence, the Gransden accession has been cultured in vitro in laboratories for half a century. Today, there are more than 13 different pedigrees derived from the original accession. Additionally, accessions from other sites worldwide were collected during the last decades. Methods and results In this study 250 high throughput RNA sequencing (RNA-seq) samples and 25 gDNA samples were used to detect single nucleotide polymorphisms (SNPs). Analyses were performed using five different P. patens accessions and 13 different Gransden pedigrees. SNPs were overlaid with metadata and known phenotypic variations. Unique SNPs defining Gransden pedigrees and accessions were identified and experimentally confirmed. They can be successfully employed for PCR-based identification. Conclusion We show independent mutations in different Gransden laboratory pedigrees, demonstrating that somatic mutations occur and accumulate during in vitro culture. The frequency of such mutations is similar to those observed in naturally occurring populations. We present evidence that vegetative propagation leads to accumulation of deleterious mutations, and that sexual reproduction purges those. Unique SNP sets for five different P. patens accessions were isolated and can be used to determine individual accessions as well as Gransden pedigrees. Based on that, laboratory methods to easily determine P. patens accessions and Gransden pedigrees are presented.